A model of digital literacy development in health care academics and the digital competency plexus - Barry Matthews (Discover Education)
Abstract The level of digital literacy development has been explored internationally. As a part of a larger doctoral thesis, the levels of digital literacy in health care academics was collected (n=52) from universities across England. The framework selected was A Health and Care Digital Capabilities Framework, and a model of development was created using ’best fit’ modelling. The result of which discovered a complex of areas that influence digital literacy development that includes technical proficiency; teaching, learning and self-development; and creativity, innovation and research. The discovered complex is either co-created with or limits the development of other areas of digital literacy. If this model is not considered when designing learning opportunities frustration may occur when the healthcare academic takes part in digital literacy development opportunities, or in the use of digital skills. A more developed digital literacy can not only improve the efficiency and efficacy of an academic, but also increase satisfaction in their role. Ensuring that skills are co-developed, or that limiting skills are developed a priori, the application of newly learnt digital skills is more effective and the academic is motivated to continue in their development.